Case Report: Occupational Dust Exposure Among Bakery Workers in Perth, Western Australia - Rumchev, Krassi; Zhao, Yun; Lee, Andy (Frontiers in Public Health, 2021)
Occupational dust exposure can occur in various settings, including bakeries. A case study was conducted in an industrial bakery in Perth, Western Australia, to assess exposure to particulate dust concentration. The factory was separated into three production zones and an office area which represented as a control zone. Results indicated that bakery workers in the production zones were exposed to higher ambient dust particle concentrations compared to those from the office environment. Coarse particles (>10 μm in aerodynamic diameter) were the predominant particle size fraction measured in all studied areas with the highest median exposure level recorded in the dough room (0.181 mg/m3, interquartile range 0.283). High personal concentration of respirable particles was also measured in the dough room (median 2.26 mg/m3) which exceeded the recommended limit of 1.5 mg/m3 and was more than 50 times higher than the concentration recorded in the office (0.04 mg/m3). The variation in dust concentrations between production zones underlines the need of more knowledge about how aerosol fractions are distributed across the production process. The findings also suggest that bakery workers are exposed to high dust levels that may increase their risk of developing respiratory diseases and the decrease of present exposure levels is imperative.